Carbene‐Stabilized Dithiolene (L0) Zwitterions. (12th September 2021) - Wang, Yuzhong; Tran, Phuong M.; Xie, Yaoming; Wei, Pingrong; Glushka, John N.; Schaefer, Henry F.; Robinson, Gregory H.
Abstract: A series of reactions between Lewis bases and an imidazole‐based dithione dimer (1 ) has been investigated. Both cyclic(alkyl)(amino)carbene (CAAC) (2 ) and N‐heterocyclic carbene (NHC) (4 ), in addition to N‐heterocyclic silylene (NHSi) (6 ), demonstrate the capability to cleave the sulphur–sulphur bonds in 1, giving carbene‐stabilized dithiolene (L 0 ) zwitterions (3 and 5 ) and a spirocyclic silicon–dithiolene compound (7 ), respectively. The bonding nature of 3, 5, and 7 are probed by both experimental and theoretical methods. Abstract : Scissions of sulphur–sulphur bonds in an imidazole‐based dithione dimer by stable Lewis bases have been investigated. While NHSi gives a spirocyclic silicon–dithiolene complex, both CAAC and NHC provide unusual carbene‐stabilized dithiolene (L 0 ) zwitterions.